SQL Server 2017 administration inside out : Video series (Inside out (Redmond, Wash.), 2018)
"In this video, database analyst and trainer Eric Johnson gives you the tools you need to manage SQL Server in your environment. You learn about the new features in SQL Server 2017, including running SQL Server on Linux. You also learn how to provision and secure Azure databases, design SQL Server tables, and tune and optimize SQL. The video wraps up by showing you how to manage data recovery and implement high-availability databases. Throughout the video, Eric explains the concepts and methodologies of managing SQL Server databases and then puts techniques into practice with visual demonstrations. With Eric as your guide, follow his detailed steps and get hands-on practice to become a more experienced--and more efficient-- database administrator."--Resource description page